View of San Francisco Bay - Roberts & Roberts, R.B.:::::::::
Description attached: When the 1775 Don Manuel de Ayala sailed through the Golden Gate, he rubbed his eyes and believed - and rightfully so - he had discovered the world's finest land-locked harbor. During 1939, thousands of more Don Manuals will move through this famed Gateway of Gold to discover, lying straight ahead in all its Aladdin-like glory the dream-like beauty of the Golden Gate International Exposition on Treasure Island. Here the world-traveler will realize he might as well have remained at home, as the whole world, with its native exoticism will be concentrated on the 400-acre Fair site. Immediate foreground shows the Golden Gate bridge, world's mightiest single-span structure beyond, to the right lies San Francisco just over the city spires is the Bay Bridge, longest in the world, connecting San Francisco with Oakland, on the far shore. Centering the picture is Treasure Island, itself.